Decoupling of chemical and isotope fractionation processes during atmospheric heating of micrometeorites. (1st May 2022) - Lampe, Seppe; Soens, Bastien; Chernonozhkin, Stepan M.; de Vega, Claudia González; van Ginneken, Matthias; Van Maldeghem, Flore; Vanhaecke, Frank; Glass, Billy P.; Franchi, Ian A.; Terryn, Herman; Debaille, Vinciane; Claeys, Philippe; et al.
Abstract: Micrometeorites experience varying degrees of evaporation and mixing with atmospheric oxygen during atmospheric entry. Evaporation due to gas drag heating alters the physicochemical properties of fully melted cosmic spherules (CSs), including the size, chemical and isotopic compositions and is thus expressed in its chemical and isotopic signatures. However, the extent of evaporation and atmospheric mixing in CSs often remains unclear, leading to uncertainties in precursor body identification and statistics. Several studies have previously estimated the extent of evaporation based on the contents of major refractory elements Ca and Al in combination with the determined Fe/Si atomic ratios. Similarly, attempts have been made to design classification schemes based on isotopic variations. However, a full integration of any previously defined chemical classification schemes with the observed isotopic variability has not yet been successful. As evaporation can lead to both chemical and isotope fractionation, it is important to verify whether the estimated degrees of evaporation based on chemical and isotopic proxies converge. Here, we have analysed the major and trace element compositions of 57 chondritic (mostly V-type) CSs, along with their Fe isotope ratios. The chemical (Zn, Na, K or CaO and Al2 O3 concentrations) and δ 56 Fe isotope fractionation measured in these particles show no correlation. The interpretation of these results is twofold: (i) isotopic and chemical fractionation are governed by distinct processes or (ii) the proxies selected for chemical and isotope fractionation are inadequate. While the initial Fe isotopic ratios of chondrites are constrained within a relatively narrow range (0.005 ± 0.008‰ δ 56 Fe), the chemical compositions of CSs display larger variability. Cosmic spherules are thus often not chemically representative of their precursor bodies, due to their small size. As oxygen isotopes are commonly used to refine the precursor bodies of meteorites, triple oxygen isotope ratios were measured in thirty-seven of the characterized CSs. Based on the relationship between δ 18 O and δ 57 Fe, the evaporation effect on the O isotope system can be calculated, which allows for a more accurate parent body determination. Using this correction method, two 'Group 4' spherules with strongly variable degrees of isotope fractionation (δ 56 Fe of ∼1.0‰ and 29.1‰, respectively) could be distinguished. Furthermore, it was observed that all CSs that probably have a OC-like heritage underwent roughly the same degree of atmospheric mixing (∼8‰ δ 18 O). This highlights the potential of including Fe isotope measurements to the regular methodologies applied to CS studies.